Sosialisasi pencegahan dan pengendalian Infeksi Saluran Nafas Akut di Wilayah XIII Koto Kampar - Rahmayati Rusnedy; Adriani Susanty; Rickha Octavia; Nofri Hendri Sandi; Ferdy Firmansyah; Armon Fernando (Universitas Mataram, 2020)
Acute Respiratory Infection (ARI) is one of the highest infectious diseases in Indonesia that can cause death. The public knowledge about the prevention and control of ARI is inadequate, so prevention efforts are needed to reduce the transmission of this infection disease. The purpose of this community service activity is to increase the knowledge of the people of Gunung Bungsu Village, Kec. XIII Koto Kampar on preventing the transmission of ARIs through preventive measures by providing education on how to use masks and proper ethics when coughing/sneezing. The method used was an interactive and participatory model by involving the community at Gunung Bungsu Village, Kec. XIII Koto Kampar. This socialization activity increased the community knowledge, showed by the enthusiasm of community at Gunung Bungsu Village, Kec. XIII Koto Kampar who actively interacts through the questions they ask to increase their understanding of ARI. Beside that, the results of the questionnaire assessment showed that the community was satisfy with the socialization of ARI prevention. This service can be useful for the prevention and control of ARI around the neighborhood.